1999
DOI: 10.1093/ajcn/69.2.250
|View full text |Cite
|
Sign up to set email alerts
|

Oral ferrous sulfate supplements increase the free radical–generating capacity of feces from healthy volunteers

Abstract: Background: Most dietary iron remains unabsorbed and hence may be available to participate in Fenton-driven free radical generation in conjunction with the colonic microflora, leading to the production of carcinogens or direct damage to colonocytes. Objective: Our aims were to measure the proportion of fecal iron available to participate in free radical generation and to determine the effect of an oral supplement of ferrous sulfate on free radical generation. Design: Eighteen healthy volunteers recorded their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
150
0
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(167 citation statements)
references
References 22 publications
9
150
0
8
Order By: Relevance
“…Earlier studies have confirmed that unabsorbed iron is concentrated in feces at levels ten-fold higher than most tissues, therefore the potential formation of the toxic hydroxyl radicals through Fenton chemistry is greatly increased in the large bowel. [21][22][23][24] There is controversy as to whether diet can dramatically influence iron stores. Experimental studies have reported that dietary iron cannot induce iron overload [25][26][27] , although a more recent study in a large American cohort found a significant positive association between dietary factors, including meat, and increased iron stores.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have confirmed that unabsorbed iron is concentrated in feces at levels ten-fold higher than most tissues, therefore the potential formation of the toxic hydroxyl radicals through Fenton chemistry is greatly increased in the large bowel. [21][22][23][24] There is controversy as to whether diet can dramatically influence iron stores. Experimental studies have reported that dietary iron cannot induce iron overload [25][26][27] , although a more recent study in a large American cohort found a significant positive association between dietary factors, including meat, and increased iron stores.…”
Section: Discussionmentioning
confidence: 99%
“…El hierro es un prooxidante que puede unirse a restos de cisteína de las proteínas y causar la formación de radicales de hidroxilo libres (128). Se ha demostrado que la ingesta de suplementos de hierro aumenta la excreción de radicales libres en las heces en individuos sanos (129). La presencia de telómeros cortos en los consumidores de suplementos de hierro podría deberse a la capacidad de generación de radicales libres y al resultante estrés oxidativo (127).…”
Section: Hierrounclassified
“…Si consideramos que la mayoría de los pacientes con enfermedad inflamatoria intestinal presentan anemia por deficiencia de hierro en alguna etapa de su enfermedad, la necesidad de tratarlos con fierro por vía oral es frecuente 37 . En sujetos sanos, a quienes se dio una suplementación de 19 mg de fierro elemental al día por un período de dos semanas, se observó que los radicales libres en las deposiciones aumentaron alrededor de 40% 38 . Así, la evidencia indica que el hierro produce estrés oxidativo intraluminal, pero no aclara si el fenómeno tiene una magnitud que puede ser manejada por los mecanismos homeostáticos que habitualmente operan en el intestino al entrar en contacto con la carga dietaria o si constituyen un riesgo per se.…”
Section: Hierro Cobre Y Enfermedad De Crohnunclassified